Fluorodeoxyglucose Positron Emission Tomography/Computed Tomography Imaging of a Patient with Squamous Cell Carcinoma of Prostate - Gonca Kara Gedik; Guler Yavas; Murat Akand; Esin Celik; Oktay Sari (Case Reports in Medicine)
Primary squamous cell carcinoma is an uncommon tumor of the prostate gland. We report a 77-year-old male patient with urinary frequency and constipation. Fine needle biopsy from prostate was suspicious of squamous cell carcinoma of the prostate. Whole body positron emission tomography/computed tomography scan revealed high fluorodeoxyglucose uptake in prostate gland. Transurethral resection confirmed the diagnosis. In contrast to prostatic adenocarcinoma, high fluorodeoxyglucose accumulation was observed in the primary tumor of the prostate gland.